Kecenderungan Narsistik sebagai Prediktor Intensitas Penggunaan Media Sosial - Kharisma Alinda Sari; Hetti Sari Ramadhani; Tatik Meiyuntariningsih (JIWA: Jurnal Psikologi Indonesia, 2026)
This study examined the relationship between narcissistic tendencies and the intensity of social media use among adolescents. The objective was to determine whether narcissistic traits and the amount of time spent on social media are related. The study employed a correlational design with a quantitative methodology. The participants were adolescents aged 15 to 19 who actively used social media. A total of 163 individuals were selected using purposive sampling. The instruments used were the narcissistic tendency scale and the social media usage intensity scale, both developed based on relevant psychological theories. Data were analyzed using a correlation technique to determine the relationship between the variables. The results indicated a tendency for higher narcissistic traits to be associated with more intense use of social media. Adolescents who exhibit narcissistic characteristics tend to use social media as a platform for self-expression and to seek approval or validation from others. This finding highlights the psychological role of social media as a space for constructing identity, especially among youth with self-focused personality traits. The study contributes to the understanding of how personality dynamics influence digital behavior in the adolescent population. Keywords: adolescent; narcissistic tendencies; self-validation; social media; usage intensity. Penelitian ini bertujuan untuk mengkaji hubungan antara kecenderungan narsistik dengan intensitas penggunaan media sosial pada remaja. Tujuan penelitian ini adalah untuk mengetahui apakah terdapat kaitan antara ciri-ciri narsistik dan jumlah waktu yang dihabiskan di media sosial. Penelitian menggunakan desain korelasional dengan pendekatan kuantitatif. Partisipan dalam penelitian ini adalah remaja berusia 15 hingga 19 tahun yang aktif menggunakan media sosial. Sebanyak 163 partisipan dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan meliputi skala kecenderungan narsistik dan skala intensitas penggunaan media sosial yang disusun berdasarkan teori psikologi yang relevan. Analisis data dilakukan menggunakan teknik korelasi untuk mengetahui hubungan antara kedua variabel. Hasil penelitian menunjukkan bahwa remaja dengan kecenderungan narsistik yang lebih tinggi cenderung memiliki intensitas penggunaan media sosial yang lebih besar. Remaja yang menunjukkan sifat narsistik menggunakan media sosial sebagai sarana untuk mengekspresikan diri dan memperoleh persetujuan dari orang lain. Temuan ini menegaskan bahwa media sosial berperan sebagai ruang psikologis dalam membangun identitas diri, terutama bagi individu dengan karakteristik kepribadian yang berpusat pada diri sendiri. Kata kunci: intensitas penggunaan media sosial; kecenderungan narsistik; media sosial; remaja; validasi diri.